Colonic Intussusception Secondary to Hereditary Angioedema. Issue 1 (13th January 2021) - Roy, Justin; Vunnam, Rama; Gorrepati, Venkata Subhash; Bethards, Deborah; McGarrity, Thomas
ABSTRACT: Hereditary angioedema (HAE) is a rare genetic disease with numerous gastrointestinal manifestations. Intussusception, although rare, has been a reported complication with documentation of bowel wall edema on endoscopy during an acute flare. With the advent of synthetic C1 esterase inhibitors, this disease has become more effectively treatable. This case report shows a HAE flare complicated by colonic intussusception, treated with C1 esterase inhibitor, with complete endoscopic resolution seen on hospital day 5. This case provides evidence that with proper medical treatment, an HAE flare with intussusception has the potential to resolve without any further need for surgical or endoscopic intervention.